Assessment of cooling methods for increased power density in electrical machines - Tighe, Chris; Gerada, C.; Pickering, Steve (2016)
A comprehensive thermal analysis of three different electrical machines is presented, with a view of identifying design aspects that can be exploited to achieve higher power density. A review of some novel cooling methods is initially made. Following this, the stator and rotor thermal resistance paths of the three selected machines are created and the individual components of each resistance path mathematically analysed to identify the parts of the machines that provide greatest potential to reduce stator and rotor temperatures. This is verified with a Design of Experiments analysis on the thermal resistance models of each. Finally, a different novel cooling method is applied to the model of each machine, demonstrating the typical temperature reductions that can be achieved.